2017
DOI: 10.26512/ser_social.v19i40.14672
|View full text |Cite
|
Sign up to set email alerts
|

Salário mínimo e acesso à alimentação e à habitação no Brasil (2004-2013)

Abstract: Tendo em vista o recente processo de valorização real do salário mínimo, este artigo tem como objetivo verificar, para o período 2004 – 2013, o acesso à alimentação e à habitação nas famílias que viviam com esse montante no Brasil. Para tanto, fundamentou-se em pesquisa bibliográfica e nos microdados das Pesquisas Nacionais por Amostra de Domicílios, do Instituto Brasileiro de Geografia e Estatística. No período observado, foram constatadas significativas melhorias no acesso à alimentação e à moradia nas famíl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…It was also observed that resided in their own home (that had been paid off) had a lower chance of experiencing food insecurity, which is possibly linked to the fact that families transfer the income that would go towards paying part of the residence or rent, for the purchase of food. According to Meressi and Steinberger [24], the excessive burden of residential house rent is an important threat to the poorest populations in terms of access to housing and food.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also observed that resided in their own home (that had been paid off) had a lower chance of experiencing food insecurity, which is possibly linked to the fact that families transfer the income that would go towards paying part of the residence or rent, for the purchase of food. According to Meressi and Steinberger [24], the excessive burden of residential house rent is an important threat to the poorest populations in terms of access to housing and food.…”
Section: Discussionmentioning
confidence: 99%
“…The experience of hunger lived in households, among adults and children, is expressed by the severe FI. No study was identified in the scientific literature that associated perception of food insecurity with diet quality by the BHEI-R. Publications related to this topic address food consumption, energy intake in specific populations [23][24][25][26]. Other authors reported that FI can affect access and food choices, impacting in the dietary quality.…”
Section: Discussionmentioning
confidence: 99%